Organic system management in low rainfall areas - Sharma, Arun K. (Indian Farming, 2015)
Organic farming is a holistic production system run with theefficient use and recycling of locally available resources. Due to scarcity of water and light soil areas it is best suitable and applicable to low rainfall areas. Some monopoly high valuecrops of this region like seed spices are having great international demand if produced organically. Organic production in low rainfall areas not only boost the economy but also sustain the productivity of natural resources. The need is to do research on development of feasible and economic technologies, development of processing and marketing infrastructure and financial as well as technical support for quality organicÂ production.